How motivational feedback increases user's benefits and continued use: A study on gamification, quantified-self and social networking. (June 2019) - Hassan, Lobna; Dias, Antonio; Hamari, Juho
Highlights: We study effect of gamification, quantified-self and social networking features. Mediating variables are affective, informational and social feedback. Dependent variables are perceived benefits and continued use intention. Context of the study is a mobile motivational information system for health. Overall, motivational design increases feedback, benefits and continued use. Abstract: With the increasing provenance of hedonic and social information systems, systems are observed to employ other forms of feedback and design than purely informational in order to increase user engagement and motivation. Three principle classes of motivational design pursuing user engagement have become increasingly established; gamification, quantified-self and social networkin g. This study investigates how the perceived prominence of these three design classes in users' use of information system facilitate experiences of affective, informational and social feedback as well as user's perceived benefits from a system and their continued use intentions . We employ survey data (N = 167) gathered from users of HeiaHeia; an exercise encouragement system that employs features belonging to the three design classes. The results indicate that gamification is positively associated with experiences of affective feedback, quantified-self with experiences of both affective and informational feedback and social networking with experiences of social feedback. Experiences of affective feedback are further strongly associated with user perceived benefits and continued use intentions, whereas experiences of informational feedback are only associated with continued use intentions. Experiences of social feedback had no significant relationship with neither. The findings provide practical insights into how systems can be designed to facilitate different types of feedback that increases users' engagement, benefits and intentions to continue the use of a system.